Suggesting a mechanism for acupuncture as a global percutaneous needle fasciotomy that respects tensegrity principles for treating fibromyalgia - Plaut, Shiloh (Frontiers in Medicine, 2023)
Acupuncture is a minimally invasive therapeutic method that uses small caliber needles while inserting them through the skin into various areas of the body. Some empirical studies find evidence to support the use of acupuncture as a treatment for certain medical conditions, however, this peculiar practice is widely considered as the domain of alternative and non-evidence-based medicine. Several mechanisms have been suggested in attempt to explain the therapeutic action of acupuncture, but the way in which acupuncture alleviates chronic non-cancer pain or psychosomatic and psychiatric disorders is not fully understood. A recent study suggested a theoretical model (coined "Fascial Armoring") with a cellular pathway to help explain the pathogenesis of myofascial pain/fibromyalgia syndrome and functional psychosomatic syndromes. It proposes that these syndromes are a spectrum of a single medical entity that involves myofibroblasts with contractile activity in fascia and aberrant extracellular matrix remodeling, which may lead to widespread mechanical tension and compression. This can help explain diverse psycho-somatic manifestations of fibromyalgia-like syndromes. Fascia is a continuous interconnected tissue network that extends throughout the body and has qualities of bio-tensegrity. Previous studies show that a mechanical action by needling induces soft tissue changes and lowers the shear modulus and stiffness in myofascial tissue. This hypothesis and theory paper offers a new mechanism for acupuncture therapy as a global percutaneous needle fasciotomy that respects tensegrity principles (tensegrity-based needling), in light of the theoretical model of "Fascial Armoring". The translation of this model to other medical conditions carries potential to advance therapies. In these days opioid overuse and over-prescription are ubiquitous, as well as chronic pain and suffering.